Bugs and Drugs: An Integrated Case-Based Microbiology-Pharmacology Session on Respiratory Infections - Melphine Harriott; Senthil Rajasekaran (Association of American Medical Colleges, 2013)
Abstract This interactive small-group session integrates microbiology of the respiratory tract with pharmacology (antimicrobials). It is intended as a review following lectures or interactive sessions in basic microbiology, respiratory microbiology, and antimicrobials. This integrated case-based microbiology and pharmacology session reinforces the basic concepts of respiratory microbiology with basic concepts of antimicrobial therapy. The cases require students to recall clinical presentations of various microbes, microbiology laboratory tests, and appropriate antimicrobials for treatment of specific pathogens. During the inaugural year of our curriculum, the students scored lower than anticipated on the microbiology and pharmacology sections of the respiratory course final exam. During the second year of our curriculum we aimed to remedy this and strengthen both disciplines with additional microbiology and pharmacology sessions, such as this. A comparison of final exam scores from the inaugural year and the second year of the respiratory course demonstrated a rise in scores for microbiology- and antimicrobial (pharmacology)-related questions.